Environmental Sustainability and Urban Growth Issues: Empirical Evidence from Osogbo Capital Territory, Nigeria - Kolawole O. Morakinyo; F. O. Eghenure; H. O. Adebiyi; J. A. Adeola (Local Engineering, 2023)
Worldwide, urban centers have continued to see exceptional increase in spatial urban growth since more than 50 years ago in the majority of emerging countries. Osogbo, the capital of Osun State, is hardly discussed despite being one of the cities in Nigeria that is quickly urbanizing. In order to establish a justification for good governance in the pursuit of environmental sustainability, the article examines challenges related to urban growth and environmental sustainability in the Osogbo Capital Territory. Four Hundred and Fifty (450) questionnaires were distributed among the residents of six (6) residential areas and 384 questionnaires were retrieved, representing 85.33%, ergo judged fit for analysis of this study. Using a Stratified Random Sampling Techniques in order to ensure a fair representation of different socio-economic groups in Osogbo, Primary Data were obtained from field surveys with the administration of questionnaires across the Three (3) neighborhood strata to include: Core Area, Intermediate Area and New Areas. A pilot survey was conducted to test the reliability of the research instruments which paved the way for the refinement of the final questionnaire. The study used the severity index test of association, mean weighted score, and percentage-based descriptive methodology. The analysis's findings indicated that urban population growth had a big impact on environmental sustainability in terms of the state of the infrastructure and facilities, people's satisfaction with the facilities that are currently available, and the environmental issues in the neighborhood that was chosen. In order to maintain our cities and ensure the future well-being of inhabitants, the paper consequently advises proper methods of crucial policies to be held in order to achieve sustainable development, as this will further promote sustainability of Nigerian cities.